2017
DOI: 10.1017/nws.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Social influence on 5-year survival in a longitudinal chemotherapy ward co-presence network

Abstract: Chemotherapy is often administered in openly designed hospital wards, where the possibility of patient–patient social influence on health exists. Previous research found that social relationships influence cancer patient’s health; however, we have yet to understand social influence among patients receiving chemotherapy in the hospital. We investigate the influence of co-presence in a chemotherapy ward. We use data on 4,691 cancer patients undergoing chemotherapy in Oxfordshire, United Kingdom who average 59.8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Apart from the coping efforts that must be done is to control the emotional pressure of children by providing understanding. Social relations have a very strong role in the optimism of cancer patients in undergoing treatment, after undergoing chemotherapy, social life will experience changes, whether it is caused by decreased body function or emotional changes in cancer patients (Banoycinova & Baskova, 2014)This is in accordance with research conducted by (Lienert et al, 2018) which states that the social changes that arise in cancer patients after chemotherapy are due to disruption of body functions which causes the participants' social activities to be limited and the participants themselves limit their social activities because they feel inadequate (Pakenham, 2012). Social support from the community is needed to foster enthusiasm and feelings of respect in the community (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Apart from the coping efforts that must be done is to control the emotional pressure of children by providing understanding. Social relations have a very strong role in the optimism of cancer patients in undergoing treatment, after undergoing chemotherapy, social life will experience changes, whether it is caused by decreased body function or emotional changes in cancer patients (Banoycinova & Baskova, 2014)This is in accordance with research conducted by (Lienert et al, 2018) which states that the social changes that arise in cancer patients after chemotherapy are due to disruption of body functions which causes the participants' social activities to be limited and the participants themselves limit their social activities because they feel inadequate (Pakenham, 2012). Social support from the community is needed to foster enthusiasm and feelings of respect in the community (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…Social support from the community is needed to foster enthusiasm and feelings of respect in the community (Wang et al, 2017). Support can come from friends, neighbors, medical personnel who handle it, which can improve the quality of life of cancer patients undergoing chemotherapy (Barthakur et al, 2017) Social support from the community shows a good quality of life for cancer sufferers (Lienert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have carried out clinical trial tests on the effect of red betel on the healing of incisions in rats, it was found that red betel leaf extract had the highest effect to help speed up the healing time of incisions performed on rats, both excision and burn wounds (Lien et al, 2015;Lienert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…16 17 Social networks are of particular import because new knowledge can lead to cascades of behaviour change, where people subsequently educate those in their social network, in what is known as social influence. [18][19][20] This has been examined in participant-driven interventions, where initially-recruited participants educate members of their social network one-on-one. 21 Characteristics such as knowing the HIV status of network members has been shown to be the most important predictor of engaging in prevention advocacy.…”
Section: Open Accessmentioning
confidence: 99%